Acute to long-term characteristics of impedance recordings during neurostimulation in humans - Cui, J; Mivalt, F; Sladky, V; Kim, J; Richner, TJ; Lundstrom, BN; Van Gompel, JJ; Wang, H-L; Miller, KJ; Gregg, N; Wu, LJ; Denison, T; et al. (2024)
Objective This study aims to characterize the time course of impedance, a crucial electrophysiological property of brain tissue, in the human thalamus (THL), amygdala-hippocampus (AMG-HPC), and posterior hippocampus (post-HPC) over an extended period.